2022
DOI: 10.1093/ejcts/ezad014
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative visualization of congenital lung abnormalities: hybridizing artificial intelligence and virtual reality

Abstract: OBJECTIVES When surgical resection is indicated for a congenital lung abnormality, lobectomy is often preferred over segmentectomy, mostly because the latter is associated with more residual disease. Presumably, this occurs in children because sublobar surgery often does not adhere to anatomical borders (wedge resection instead of segmentectomy), thus increasing the risk of residual disease. This study investigated the feasibility of identifying eligible cases for anatomical segmentectomy by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…A decade has passed since the initial reports on 3D-CT image-guided lung resection ( 54 59 ) and 3D-CT imaging has become widely implemented with results of prospective multicenter studies now being reported ( 60 ). The current surge of 3D-CT imaging analysis shows that the field is still growing, with the technology continuing to improve and now even being combined with virtual reality and artificial intelligence ( 61 , 62 ). Future studies using these new and innovative methodologies will continue to refine our understanding of lung anatomy while enhancing our ability to perform safe and effective surgical resections.…”
Section: Discussionmentioning
confidence: 99%
“…A decade has passed since the initial reports on 3D-CT image-guided lung resection ( 54 59 ) and 3D-CT imaging has become widely implemented with results of prospective multicenter studies now being reported ( 60 ). The current surge of 3D-CT imaging analysis shows that the field is still growing, with the technology continuing to improve and now even being combined with virtual reality and artificial intelligence ( 61 , 62 ). Future studies using these new and innovative methodologies will continue to refine our understanding of lung anatomy while enhancing our ability to perform safe and effective surgical resections.…”
Section: Discussionmentioning
confidence: 99%
“…The potential clinical feasibility of a combined VR/AR and AI approach has also been demonstrated in fairly recent studies done by Sadeghi et al and Bakhuis et al which showcased the use of a combined VR and AI strategy in providing better visualization of their patient’s’ pulmonary anatomy. (54,55)…”
Section: Discussionmentioning
confidence: 99%
“…Thoracoscopic anatomical segmentectomy is the ideal surgical option for removing the lesion while preserving normal lung tissue within the lobes and protecting lung function. Nevertheless, non-anatomic lung preservation surgery is more likely to have residual lesions than lobectomy [10,11].…”
Section: Introductionmentioning
confidence: 99%